Effect of age of dam on weight of calf in the genetic assessment of Zebu cattle in random regression models - Jorge Luis Ferreira; Fernando Brito Lopes; Tiago Bresolin; José Américo Soares Garcia; Silvia Minharro; Raysildo Barbosa Lôbo (Acta Scientiarum. Animal Sciences, 2015)
Current analysis estimated co-variance components and genetic parameters for growth traits by random regression models taking into consideration the cow’s age on the weight of calves. Genealogical data and records on weights of male and female Zebu cattle, born between 1993 and 2011, were provided by the National Association of Breeders and Researchers (ANCP). Different models were compared by Akaike and Bayesian criteria. Legendre’s orthogonal polynomials were used to model the direct and maternal genetic effects of maternal and animal permanent environmental effects. Joint modeling of cow age at the moment their progenies were weighed resulted in more accurate estimates of co-variance components and genetics parameters. Co-variance functions of the cow age retrieved the dam effect on real performance of the progenies, reduced biases, improved parameter estimates and predicted breeding rates.